2021
DOI: 10.7759/cureus.14918
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast in the Management of Disseminated Granuloma Annulare

Abstract: Granuloma annulare (GA) is a common inflammatory skin condition that manifests as annular skin colored to erythematous papules and plaques. Disseminated GA is a subtype of GA that presents with diffuse cutaneous involvement. While topical and intralesional corticosteroids and phototherapy have been used as therapies for GA, there is no consensus on the best course of treatment for GA. Apremilast is a phosphodiesterase 4 (PDE4) inhibitor that has been Food and Drug Administration (FDA) approved for psoriasis, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Bishnoi et al then reported a case series of four GA patients treated with apremilast, three of whom experienced a reduction in lesion number and one patient who experienced decreased erythema and pruritus; in all four patients, response to apremilast was seen within 6–8 weeks of initiating treatment [ 70 ]. Joshi and Tschen reported an additional case where apremilast led to near total resolution of lesions in seven months [ 71 ]. Most recently, Hansel et al reported two patients who also experienced marked improvement of their GA within 8 weeks of treatment [ 72 ].…”
Section: Review Of Management Optionsmentioning
confidence: 99%
“…Bishnoi et al then reported a case series of four GA patients treated with apremilast, three of whom experienced a reduction in lesion number and one patient who experienced decreased erythema and pruritus; in all four patients, response to apremilast was seen within 6–8 weeks of initiating treatment [ 70 ]. Joshi and Tschen reported an additional case where apremilast led to near total resolution of lesions in seven months [ 71 ]. Most recently, Hansel et al reported two patients who also experienced marked improvement of their GA within 8 weeks of treatment [ 72 ].…”
Section: Review Of Management Optionsmentioning
confidence: 99%
“…At the time of our literature review completion, there were nine published reports describing the use of oral apremilast to treat GA. All patients experienced at least partial improvement in a number of lesions, erythema of lesions, and pruritus. Two thirds of these patients had not previously been responsive to topical, systemic, and/or intralesional corticosteroids ( Bishnoi et al., 2019 ; Blum and Altman, 2019 ; Hansel et al., 2021 ; Joshi and Tschen, 2021 ). The exact mechanism of apremilast in GA is not clear but may be related to indirect inhibition of TNF and/or IFN-γ signaling.…”
Section: Gamentioning
confidence: 99%
“…Efficacy of apremilast in generalized GA has been documented in several small case series and case reports (Table 9). [41][42][43][44] Larger placebo-controlled trials are required to establish the role of apremilast in generalized GA.…”
Section: Generalized Granuloma Annularementioning
confidence: 99%